Effects of Convection and Microwave Drying Schemes on the Characteristics and Sound Absorption of Acoustic Oil Palm Boards - Panya Dangvilailux; Jarruwat Charoensuk (My University, 2017)
This research aimed to develop economical, high-performance acoustic oil palm boards (OPB) using the convection (CV) and microwave (MW) wood drying technologies under variable thermal conditions. The results revealed that the CV and MW oven temperatures were positively correlated with moisture desorption but inversely correlated with drying time. The CV heating temperatures were inversely and positively correlated with the density and volumetric shrinkage, respectively, and the MW power output was positively correlated with density and shrinkage. Thus, the MW-treated OPB specimens exhibited stronger mechanical characteristics than the CV-treated OPB specimens. Importantly, the CV-treated OPB specimens acoustically outperformed the MW-treated counterparts, as evidenced by the former’s higher noise reduction coefficients (NRC). This phenomenon was attributed to the abundance of fissures between the vascular bundles and the parenchyma. Thus, the CV technology was more operationally and economically suited to the high-performance acoustic OPB.
Keywords: Wood Treatment and Properties